Psychology through critical auto-ethnography : academic discipline, professional practice and reflexive history - Parker, Ian, 1956- (London [etc.] Routledge, 2020)
This unique book is an insider account about the discipline of psychology and its limits, introducing key debates in the field of psychology around the world today by closely examining the problematic role the discipline plays as a global phenomenon. Ian Parker traces the development of critical psychology' through an auto-ethnographic narrative in which the author is implicated in what he describes, laying bare the nature of contemporary psychology. In five parts, each comprising four chapters, the book explores the student experience, the world of psychological research, how psychology is taught, how alternative critical movements have emerged inside the discipline, and the role of psychology in coercive management practices. Providing a detailed account of how psychology actually operates as an academic discipline, it shows what teaching in higher education and immersion in research communities around the world looks like, and it culminates in an analytic description of institutional crises which psychology provokes. A reflexive history of psychology's recent past as a discipline and as a cultural force, this book is an invaluable resource for anyone thinking of taking up a career in psychology, and for those reflecting critically on the role the discipline plays in people's lives
Bibliografía: páginas 323-329
Keywords: Psicología -- Investigación -- Metodología; Psicología social